Patterns of Interpersonal Communication Students through the Class Tarkiz Quran Memorizers - Nofha Rina; Jenny Ratna Suminar; Ninis Agustini Damayani; Hanny Hafiar (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2019)
This research came from the uniqueness of the Alquran Elementary School (SDQu) in Indonesia which was interesting to be studied. This study highlighted the instructional communication orientation of students through an analysis of interpersonal communication in learning activities in the Tarkiz classroom. Using the case study method, we employed the theoretical lens of social construction, symbolic interaction, and social cognitive as a way to capture the truth and explore this phenomenon more to make model of interpersonal communication in the field of instructional communication. Findings are discussed effective instructional communication between students and teachers Tarkiz created conducive learning for students to developed an interpersonal communication model on the openness of student and teacher, the interaction of the environment, and equality of student and teacher. This study makes contributions to interpersonal communication in practice. Penelitian ini membahas keunikan Sekolah Dasar Alquran (SDQu) di Indonesia yang menarik untuk dipelajari. Penelitian ini menyoroti orientasi komunikasi instruksional siswa melalui analisis komunikasi interpersonal dalam kegiatan pembelajaran di kelas Tarkiz. Menggunakan metode studi kasus, kami menggunakan lensa teoritis konstruksi sosial, interaksi simbolik, dan kognitif sosial sebagai cara untuk menangkap kebenaran dan mengeksplorasi fenomena ini lebih untuk membuat model komunikasi interpersonal di bidang komunikasi instruksional. Temuan dibahas komunikasi instruksional yang efektif antara siswa dan guru Tarkiz menciptakan pembelajaran yang kondusif bagi siswa untuk mengembangkan model komunikasi interpersonal pada keterbukaan siswa dan guru, interaksi lingkungan, dan kesetaraan siswa dan guru. Penelitian ini memberikan kontribusi pada komunikasi interpersonal dalam praktik.